Intensification of degradation of methomyl (carbamate group pesticide) by using the combination of ultrasonic cavitation and process intensifying additives - Raut-Jadhav, Sunita; Pinjari, Dipak V.; Saini, Daulat R.; Sonawane, Shirish H.; Pandit, Aniruddha B. (Ultrasonics Sonochemistry, 2016)
In the present work, the degradation of methomyl has been carried out by using the ultrasound cavitation (US) and its combination with H2O2, Fenton and photo-Fenton process. The study of effect of operating pH and ultrasound power density has indicated that maximum extent of degradation of 28.57% could be obtained at the optimal pH of 2.5 and power density of 0.155 W/mL. Application of US in combination with H2O2, Fenton and photo-Fenton process has further accelerated the rate of degradation of methomyl with complete degradation of methomyl in 27 min, 18 min and 9 min respectively. Mineralization study has proved that a combination of US and photo -Fenton process is the most effective process with maximum extent of mineralization of 78.8%. Comparison of energy efficiency and cost effectiveness of various processes has indicated that the electrical cost of 79892.34 Rs./m(3) for ultrasonic degradation of methomyl has drastically reduced to 2277.00 Rs./m(3), 1518.00 Rs./m(3) and 807.58 Rs./m(3) by using US in combination with H2O2, Fenton and photo-Fenton process respectively. The cost analysis has also indicated that the combination of US and photo-Fenton process is the most energy efficient and cost effective process. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Fenton; Hydrogen peroxide; Methomyl; Photo-Fenton; Synergistic coefficient; Ultrasound cavitation

Improved efficiency of DSSC using combustion synthesized TiO2 - Umale, Sanjivani; Sudhakar, V.; Sontakke, Sharad M.; Krishnamoorthy, K.; Pandit, Aniruddha B. (Materials Research Bulletin, 2019)
Combustion synthesis method is an economic, one step and an effective method for the synthesis of nanomaterials. In this work, titanium dioxide nanoparticles were synthesized by combustion method. The synthesized material was characterized by XRD, SEM and BET. Dye sensitized solar cell was fabricated using the synthesized material and its performance was compared with the solar cell fabricated using commercial TiO2. In order to evaluate the photovoltaic performance of DSSCs, photocurrent density to photovoltage (J-V) characteristic and electrochemical impedance spectroscopy (EIS) measurements were carried out. The DSSC fabricated using combustion synthesized and commercial TiO2 exhibited a power conversion efficiency of 6.11% and 6.62%, respectively. Combustion synthesized TiO2 which displayed similar efficiency to that of commercial material is least studied in the literature for solar cell applications.
Keywords: Combustion synthesis; Dye sensitized solar cell; TiO2